(untitled) (The Agriculturists, 2012)
A study was conducted to determine the direct and residual effects of phosphate rock (PR) on the growth and yield of wheat cv. Kanchan during Rabi season of 2004-2005 at the Bangladesh Agricultural University farm, Mymensingh. The experiment was designed with four treatments and was laid out in a Randomized Complete Block Design (RCBD) with four replications. The treatments were: T1: control (0 kg P ha-1), T2: PR (26 kg P ha-1), T3: TSP (26 kg P ha-1), and T4: PR (210 kg P ha-1 applied in previous crop to cover 6 succeeding crops). Dry matter yield at panicle initiation (PI) stage was significantly influenced by the treatments. Effective tillers hill-1 and grains panicles-1 varied significantly with P treatments. The highest grain yield (3.10 t ha-1) and straw yield (5.54 t ha-1) were found in T3 treatment. Economic analysis demonstrated that the highest net benefit of Tk. 24,788 ha-1 was obtained in T3 treatment which was followed by Tk. 22,964 ha-1 and Tk.12,292 ha-1 in T4 and T2, respectively. The highest net benefit was obtained from T3 treatment due to higher grain and straw yields. DOI: http://dx.doi.org/10.3329/agric.v10i1.11062 The Agriculturists 2012; 10(1): 31-37